Toward optimising reproductive output of Eristalis tenax (Diptera: Syrphidae) for commercial mass rearing systems - Upchurch, Annick; Spurr, Cameron J.; Quarrell, Stephen R.; Rowbottom, Raylea M.; Allen, Geoff R. (Austral entomology, 2023)
Developing mass rearing systems for the drone fly, Eristalis tenax, is a crucial step toward its use as a complementary commercial pollinator. To meet the timing of commercial needs for E. tenax, there is significant value to both predicting and managing reproductive output and development within the rearing protocol. To help achieve this, our study focuses on the laboratory manipulation of adult mating and the timing of the development of eggs in E. tenax. To stagger colony cohorts, egg rearing temperatures ranging from 12 to 30°C were found to be suitable for both successful egg development and hatching viability (97 to 28.3 h to first hatch, respectively). The mating window for E. tenax females was established to commence from 2 weeks post eclosion and reached 75 ± 11% mated at 7 weeks. Reproductive output over 12 weeks was assessed in separate cage manipulation trials: (1) varying the sex ratio with 20:40, 30:30 and 40:20 female and male flies respectively per cage and (2) varying the adult density per cage with 15:15, 30:30, 60:60 and 120:120 female and male flies per cage. Female percentage mated and egg cluster size, which averaged 200.6 ± 4.3 eggs per cluster, did not change between treatments in the sex ratio and density trials. Egg cluster output per female was significantly reduced for treatments across both trials, which had more than 30 females in a cage. A stocking rate of 15:15 produced 86% more eggs per female than expected, a percentage well above that of all other treatments. However, the highest stocking density produced the most eggs when assessed at a per cage level. Fly survival was significantly different between the sexes across both trials with males dying earlier in cages stocked with more females than males. Although the fly colonies were held at constant temperatures and light conditions for 6 months, we found evidence of endogenous overwintering behaviours among flies resulting in lower mating rates, egg hatching success and greater longevity among flies studied over winter.